(untitled) (Dermatology Reports, 2022)
To the Editor: Limited evidence on the use of biologic treatments in psoriatic patients with a history of malignancy is currently available in the literature. The recently published European guidelines recommend the use of anti-TNF, anti-IL17, and anti-23 biological drugs in this special population after discussion case-by-case with a cancer-specialist [...].